DESIGN GET UP SYSTEM INFORMATION MANAGEMENT FOR MSMEs - Khairuvi Jannatu Sabila BR Pasaribu; Muhammad Irwan Padli Nasution (Young Journal of Social Sciences and Humanities, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting Indonesia’s economic growth. Despite this importance, many MSMEs still struggle with operational management, especially in recording transactions, managing inventory, and preparing financial reports. These processes are often carried out manually, resulting in low efficiency, frequent errors, and delays in making important business decisions. This research aims to design and develop a web based Management Information System (MIS) that can assist MSMEs in managing their data in an integrated and real time manner. The system is intended to be simple, affordable, and suitable for the needs and capabilities of small businesses. Using a descriptive analytical approach, this study examines both functional and non functional system requirements, designs the system architecture, develops a prototype, and evaluates its potential benefits. The evaluation is conducted through literature analysis and limited trials on selected MSMEs. The research findings show that the proposed MIS can streamline key business processes such as sales recording, inventory control, and basic financial reporting. By providing faster access to accurate information, the system has the potential to improve operational efficiency and support better decision making for MSME owners.